2019
DOI: 10.3390/catal9110929
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Cu/SSZ-13 NH3-SCR Catalyst by Exposure to CO, H2, and C3H6

Abstract: Lean nitric oxide (NOx)-trap (LNT) and selective catalytic reduction (SCR) are efficient systems for the abatement of NOx. The combination of LNT and SCR catalysts improves overall NOx removal, but there is a risk that the SCR catalyst will be exposed to high temperatures and rich exhaust during the LNTs sulfur regeneration. Therefore, the effect of exposure to various rich conditions and temperatures on the subsequent SCR activity of a Cu-exchanged chabazite catalyst was studied. CO, H2, C3H6, and the combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…High temperature in presence of water vapor is known to degrade the crystallinity of the zeolite structure, and at very high temperatures, the structure collapses [2,31], which urges the development of highly stable zeolites. The detrimental effect of reducing treatment on the copper dispersion and the subsequent SCR activity has been revealed by Auvray et al [6,32]. It was shown that exchanged copper ions tend to agglomerate in larger particles under the action of hydrogen.…”
Section: Regeneration In Scr Conditions: Standard Scrmentioning
confidence: 97%
“…High temperature in presence of water vapor is known to degrade the crystallinity of the zeolite structure, and at very high temperatures, the structure collapses [2,31], which urges the development of highly stable zeolites. The detrimental effect of reducing treatment on the copper dispersion and the subsequent SCR activity has been revealed by Auvray et al [6,32]. It was shown that exchanged copper ions tend to agglomerate in larger particles under the action of hydrogen.…”
Section: Regeneration In Scr Conditions: Standard Scrmentioning
confidence: 97%
“…Both catalysts show poor NOx reduction activity up to 175 °C; however, the aged IrRu/Al 2 O 3 reveals higher NOx conversion by CO between 200 and 250 °C than the aged Cu/CHA. As the reaction temperature increases beyond this, the NOx reduction activity of a-IrRu/Al 2 O 3 by CO starts to decrease, while a-Cu/CHA showed higher activity although NH 3 can be oxidized by O 2 . Note that low temperature lean NOx reduction has been commonly regarded as a distinct area of urea (NH 3 )/SCR technology in the automotive aftertreatment system to date.…”
Section: Resultsmentioning
confidence: 99%
“…Olsson et al studied the deactivation of the Cu/SSZ-13 catalyst that is commonly used for NH 3 -SCR by exposing it to CO, H 2, and C 3 H 6 [18], and they proposed that the reason for the increased deactivation observed in mild rich conditions was the transformation of the Cu species. These centres evolved from active isolated Cu 2+ , balancing two negative charges of Al atoms in the zeolite framework, to inactive [CuOH] + connected to one Al atom together with the formation of Cu clusters.…”
mentioning
confidence: 99%